2006
DOI: 10.1093/heapro/dal024
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Healthy Cities' principles and strategies: an evaluation of the Israel Healthy Cities Network

Abstract: The Israel network of Healthy Cities has been operating since 1990, and the first evaluation of its performance was carried out in 2004. The objectives were to evaluate the level of implementation of the 'Healthy Cities' principles and strategies in each network city and to assess the contribution of the network to its member cities. Coordinators of 18 active healthy cities participated in the study by completing a questionnaire with the aid of key informants in the municipality. The survey covered six dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…Whereas cities in low-income countries could still struggle with providing basic infrastructure like adequate waste disposal and access to clean water, cities in richer countries were able to focus on building networks and establishing inter-sector collaborations (Harpham, Burton, & Blue, 2001). Overall, evaluations reveal that success is highly dependent on political and material support for the ideas and principles of the Healthy City (Donchin, Shemesh, Horowitz, & Daoud, 2006). Aronson, Norton, and Kegler (2007) found that conflicting views regarding the importance of intervention on social and living conditions, versus intervention on individuals' lifestyle, were reduced through implementing a healthy cities approach.…”
Section: Evaluations Of the Healthy City Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas cities in low-income countries could still struggle with providing basic infrastructure like adequate waste disposal and access to clean water, cities in richer countries were able to focus on building networks and establishing inter-sector collaborations (Harpham, Burton, & Blue, 2001). Overall, evaluations reveal that success is highly dependent on political and material support for the ideas and principles of the Healthy City (Donchin, Shemesh, Horowitz, & Daoud, 2006). Aronson, Norton, and Kegler (2007) found that conflicting views regarding the importance of intervention on social and living conditions, versus intervention on individuals' lifestyle, were reduced through implementing a healthy cities approach.…”
Section: Evaluations Of the Healthy City Networkmentioning
confidence: 99%
“…The role of individual project ambassadors and coordinators and their capacity to facilitate engagement was examined in several evaluations (e.g., Donchin et al, 2006;Harpham et al, 2001). One of the major challenges identified was a lack of resources following the Project, as well as the need to develop overarching evaluation systems and theories to integrate knowledge and develop interventions based on evidence (Rychetnik et al 2012;Pluemer, Kennedy, & Trojan, 2010).…”
Section: Evaluations Of the Healthy City Networkmentioning
confidence: 99%
“…The Israeli network published their evaluation of 18 active healthy cities members. 18 The cities were assessed on six criteria (see Figure 4). Political support, together with the coordinators' building capacity, was found to be significant facilitators for sustaining successful healthy cities policies.…”
Section: Organisation Of National Networkmentioning
confidence: 99%
“…Community participation proved important in ensuring that comprehensive PHC programs attended to issues of equity (access, outcome) in Australian cases, and in Middle East Healthy Cities projects (Donchin, Shemesh, Horowitz, & Daoud, 2006). This suggests that countries with broadly social democratic politics and openness to citizen engagement (including advocacy) are more likely to support a comprehensive PHC approach.…”
Section: How Does the Political Context Affect The Comprehensiveness mentioning
confidence: 99%